2001
DOI: 10.1046/j.1525-1497.2001.016007427.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a focused educational intervention on resident evaluations from faculty

Abstract: OBJECTIVE:To improve the quality and specificity of written evaluations by faculty attendings of internal medicine residents during inpatient rotations. DESIGN:Prospective randomized controlled trial.SETTING: Four hospitals: tertiary care university hospital, Veterans' Administration hospital, and two community hospitals.PARTICIPANTS: Eighty-eight faculty and 157 residents from categorical and primary-care internal medicine residency training programs rotating on inpatient general medicine teams. INTERVENTION:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 23 publications
(41 reference statements)
4
61
3
1
Order By: Relevance
“…Participant faculty members were less likely to give residents ratings of 8 or 9 (reduced leniency error). Our findings are consistent with other research that shows rater training results in changes in how faculty rate residents when using the ABIM global rating form 13 and the Mini Clinical Evaluation Exercise (mini-CEX).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Participant faculty members were less likely to give residents ratings of 8 or 9 (reduced leniency error). Our findings are consistent with other research that shows rater training results in changes in how faculty rate residents when using the ABIM global rating form 13 and the Mini Clinical Evaluation Exercise (mini-CEX).…”
Section: Discussionsupporting
confidence: 91%
“…The use of videotaped scenarios in faculty development has been described in the literature as an effective teaching tool. 1,13 Frame-of-reference training was integrated and distributed among curriculum meetings, annual program review, and clinical competency committee meetings, during which examples and consistency of observable behaviors related to the Milestones were discussed and related to descriptive anchors on the rating scale. To be designated as a ''faculty development participant,'' an individual needed to attend at least 1 of the performance dimension training and 1 of the frame-ofreference training sessions.…”
Section: Bottom Linementioning
confidence: 99%
“…3 Fortunately, studies have found that faculty development can modestly improve the quality of written and oral feedback. 8,32,37 Several specific recommendations emerge from this study that can help guide faculty development in providing feedback. First, faculty should understand the value of providing written comments that are multiple in number and scope.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Despite the central role and clear benefits of direct observation, its implementation in GME has proved challenging. [12][13][14][15][16] Studies indicate that little time is spent conducting direct observation during an average medical workday, 12 and a substantial percentage of residents state that they have never been directly observed doing certain important clinical tasks. 14,15 Barriers to frequent use include limited faculty time, faculty attention required toward clinical tasks, trainee reluctance to be observed, and concerns about the impact on the patient-resident relationship.…”
Section: Introductionmentioning
confidence: 99%